Knowledge of midwives about clinical trials - Dominka Wieczorek; Anna Staniszewska (Kazimierz Wielki University, 2019)
Introduction: Proper level of knowledge of midwives on the subject of clinical trials is influenced by the participant's safety and the quality of conducted clinical trials. Aim: The aim of the study was to assess midwives knowledge of clinical trials. Material and method: The study involved 105 midwives, at the age of 20-54years. The method of a diagnostic survey was used. The study was conducted in period April - December 2018 year. Results: The majority of respondents - 81% (n=85) knew the correct definition of the clinical trial. The most important benefit of clinical trials for the study group was "creating new treatment standards" (69,5%, n=74), and the greatest risk resulting from clinical trials "was" the possibility of adverse events and events "(92,4%, n=97). Conclusions: Midwives knowledge about clinical trials is on a sufficient level.